2014
DOI: 10.1111/irv.12241
|View full text |Cite
|
Sign up to set email alerts
|

Neurological events related to influenza A (H1N1) pdm09

Abstract: ObjectivesTo review neurological complications after the influenza A (H1N1) pdm09, highlighting the clinical differences between patients with post-vaccine or viral infection.DesignA search on Medline, Ovid, EMBASE, and PubMed databases using the keywords “neurological complications of Influenza AH1N1” or “post-vaccine Influenza AH1N1.”SettingOnly papers written in English, Spanish, German, French, Portuguese, and Italian published from March 2009 to December 2012 were included.SampleWe included 104 articles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 114 publications
1
37
0
2
Order By: Relevance
“…Other neurologic manifestations of influenza are now known to include acute disseminated encephalomyelitis (ADEM), and acute necrotizing encephalopathy (ANE) [8]. According to a study done be Cardenas et al, fatal cases and permanent neurological sequelea were reported in 11% of patients with influenza related neurological complications [4]. This number includes also post-vaccination complications and occurred in all age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other neurologic manifestations of influenza are now known to include acute disseminated encephalomyelitis (ADEM), and acute necrotizing encephalopathy (ANE) [8]. According to a study done be Cardenas et al, fatal cases and permanent neurological sequelea were reported in 11% of patients with influenza related neurological complications [4]. This number includes also post-vaccination complications and occurred in all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…In March 2010, almost all countries reported cases of influenza A (H1N1) and more than 17,700 deaths (laboratory confirmed cases) had been documented [1]. Up to date, there are no accurate data regarding the global frequency of neurological complications related to this disease [4]. The incidence of neurological complications in influenza A (H1N1) pdm09 was estimated to be 3.7% of the total number of patients confirmed to have influenza A (H1N1) pdm09 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines reported to be associated with ASIA syndrome include several adjuvants among which AS04 [29,30,143], Alum [105,144], AS03 and MF59 [145][146][147][148][149]. This indicates that, despite the different mechanism of actions, all adjuvants may determine the ASIA syndrome.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Zum Ausschluss einer Influenza-assoziierten Myokarditis empfehlen sich bei Patienten mit schwerer Erkrankung oder gleichzeitig bestehenden kardialen Beschwerden (Brustschmerz, Rhythmusstörungen, neu aufgetretene Herzinsuffizienz) die Durchführung eines EKG sowie die Bestimmung kardialer Biomarker (Troponin). Die relative Häufigkeit anderer, insbesondere neurologischer Komplikationen, ist vergleichsweise schlecht untersucht [6]. ▶ Tab.…”
Section: Klinikunclassified